PEDAGOGICAL POTENTIAL OF USING ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH - Василевська, Тетяна (SWorldJournal, 2026)
Modern education sets itself the task not only of teaching students foreign languages, but also of developing their intercultural communicative competence. In contemporary conditions, artificial intelligence is becoming a powerful educational tool, openi